High Rates of Overuse-Related Structural Abnormalities in the Lumbar Spine of Youth Competitive Alpine Skiers: A Cross-sectional MRI Study in 108 Athletes. Issue 5 (29th May 2020) - Peterhans, Loris; Fröhlich, Stefan; Stern, Christoph; Frey, Walter O.; Farshad, Mazda; Sutter, Reto; Spörri, Jörg
Background: Alpine ski racing is known as a sport with unfavorable spinal loads and high rates of back overuse injuries at the elite level. However, little is known about overuse-related structural abnormalities occurring in the spine of youth athletes. Purpose: To describe the prevalence of abnormal magnetic resonance imaging (MRI) findings in the lumbar spine of youth competitive alpine skiers within the U16 category (under 16 years) with respect to sex, height growth, multifidus size, increasing age, and clinical relevance. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 108 youth competitive alpine skiers aged 13 to 15 years underwent MRI examination of the lumbar spine and measurement of the multifidus cross-sectional area on a 3-T Magnetom Prisma scanner. Complementary assessments included the determination of anthropometrics and biological maturation. Athletes were classified as symptomatic when, pursuant to the Oslo Sports Trauma Research Center questionnaire on health problems, at least 1 substantial back overuse–related health problem episode had been registered during the 12 months before the MRI examination. Results: Of the analyzed youth skiers, 37.0% presented with ≥1 abnormal MRI finding in the lumbar spine. The most prevalent findings in both sexes were disc degeneration (23.1%), Schmorl nodes (19.4%), end plate changes (10.2%), and pars interarticularis anomalies (10.2%); the pars interarticularis anomalies occurred exclusively in males. A smaller relative lumbar multifidus cross-sectional area was related to more frequent occurrence of disc protrusions ( P = .018; R 2 = 0.116) and end plate changes ( P = .024; R 2 = 0.096). Overall, the occurrence of abnormal MRI findings in the lumbar spine increased with age ( P = .034; R 2 = 0.054). Disc degeneration (particularly disc dehydration and disc protrusion) were significantly more prevalent in symptomatic versus asymptomatic athletes ( P < .05 for all). Conclusion: As early as age 15 years or younger, competitive alpine skiers demonstrated distinct overuse-related structural abnormalities in the lumbar spine, with some of them being clinically relevant and restrictive of sports participation. As sex, height growth, multifidus size, and increasing age seem to play an important role for the occurrence of such abnormalities, considering these factors might be essential for prevention.